Answer:
x-y=-2
Step-by-step explanation:
Divide both sides if the equations by 3.
(3y-3x)÷3=6÷3
y-3x÷3=2
calculate the quotient
y-x=2
multiply both sides of the equation bub -1
-1x(-x)-1y=-1x2
any expression multiplied by -1
x-1y=-1x2
any expression multiplied by 1 remains the same.
x--y=-1x2
x-y=-2
Answer:
The second one: r x-axis. R 90(x,y)
Step-by-step explanation:
You can see that from ABC to A'B'C', it's rotated a positive 90 degrees. then, from A'B'C' to A"B"C", reflected across x-axis. and when writing the transformation, it goes by last to first. that's why the R 90 comes first.
<span>1. Find the magnitude and direction angle of the vector.
2. Find the component form of the vector given its magnitude and the angle it makes with the positive x-axis.
<span>3. Find the component form of the sum of two vectors with the given direction angles.</span></span>
This is a formula if you need one. DON'T forget to cross-multiply
3/4 = x/12
X= 22.5 get the x by itself by dividing by 2